Stafne bone cavity with ectopic salivary gland tissue in the anterior of mandible - Parviz Deyhimi; Soheila Darisavi; Saeideh Khalesi (Wolters Kluwer Medknow Publications, 2016)
Stafne bone cavities (SBCs) are uncommon well-demarcated defects of the mandible, which often occur in the posterior portion of the jaw bone and are usually asymptomatic. Furthermore, SBC is found in men aged 50-70-year-old. Anterior mandibular variants of SBC are very rare. This article describes a case of anterior SBC in a 45-year-old man that resembled endodontic periapical lesions. Upon histopathological examination, it turned out to be a normal salivary gland tissue.